Cartola - Ferreira, Lirio; Lacerda, Hilton (Brazil : Bessa, Celia, 2006)
Cartola—The Samba Legend, about one of the most important composers of Brazilian music, is a history of samba and its relation to capoeira (a Brazilian martial art/dance), the Olympia bar scene in Rio de Janeiro, the favelas, and the formation of the famous Samba Schools. Using recreated scenes; reminiscences of musicians and people who knew Cartola; early footage of Cartola playing, performing, and composing; and fabulous found footage of early carnivals and parades, the film fashions a love letter to the city of Rio and a powerful reflection on the construction of national memory and identity.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films